Karakteristik Genus Bakteri Pada Karkas Ayam Broiler Dari Swalayan di Kota Pontianak - Diah Wulandari Rousdy, Prianti Rahmawati (Universitas Tanjungpura, 2018)
The availabilityÂ of nutrients in chicken carcasses can cause chicken meat to be an excellent medium for the growth of pathogenic and non-pathogenic bacteria. This study aims to determine the characteristics of the bacterial genus in broiler chicken carcasses from supermarkets in Pontianak City. Based on the results of the study found 23 bacterial isolates in broiler chicken carcass samples from supermarkets in Pontianak City, which included members of the Aeromonas, Acetobacter, Alcaligenes, Amphibacillus, Bacillus, Brevibacterium, Camphylobacter, Carnobacterium, Erwinia, Â Erysipelothrik, Eubacterium, Hafnia, Kluyvera, Klebsiella, Kurthia, Lactobacillus, Listeria, Proteus, Pseudomonas, Shigella, Sporolactobacillus, Serratia, and Â Yersinia.